Pelatihan Videografi sebagai Media Presentasi Tugas Akhir Mahasiswa Pendidikan Bahasa Indonesia - Ginting, Reza Pahlevi; Mahsa, Masithah; Trisfayani, Trisfayani; Safriandi, Safriandi; Najla, Rizky Rana Sastika; Maghfirah, Riezka; Shabri, Ismail; Salsabila, Salsabila (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
The "Videography Training as a Presentation Medium for Final Projects for Indonesian Language Education Students" at Universitas Malikussaleh aims to enhance students’ skills in utilizing multimedia technology as an academic presentation tool. This training covers using CapCut for video editing and Canva for template design, supporting students in creating effective and engaging final project presentations. The training method combines theoretical instruction and hands-on practice, focusing on essential techniques in video capture, visual arrangement, and audio-visual editing that facilitate clear and informative communication. The training was attended by 20 students and held at the Faculty of Teacher Training and Education Building, Universitas Malikussaleh. The training results demonstrated a significant improvement in students' skills using CapCut and Canva, especially in adding text, overlays, audio effects, and other graphic elements that enhance the aesthetic quality and professionalism of their presentations. Additionally, these applications encourage students to be more creative in constructing visual narratives that effectively reinforce the academic messages they aim to convey. Thus, this training not only equips students with relevant technical skills but also supports their preparedness for a job market increasingly demanding multimedia competence. This activity is expected to serve as a long-term investment in preparing graduates who are adaptable to the evolving digital technology landscape in education and communication.ABSTRAKKegiatan “Pelatihan Videografi sebagai Media Presentasi Tugas Akhir Mahasiswa Pendidikan Bahasa Indonesia” di Universitas Malikussaleh bertujuan untuk meningkatkan keterampilan mahasiswa dalam memanfaatkan teknologi multimedia sebagai media presentasi akademis. Pelatihan ini mencakup penggunaan aplikasi CapCut untuk editing video dan Canva untuk pembuatan template, guna mendukung mahasiswa dalam menyusun presentasi tugas akhir yang efektif dan menarik. Metode pelatihan yang diterapkan mengombinasikan teori dan praktik langsung, dengan fokus pada teknik dasar pengambilan gambar, pengaturan visual, serta pengeditan audio-visual yang mendukung alur komunikasi yang jelas dan informatif. Pelatihan ini diikuti oleh 20 mahasiswa dan berlangsung di Gedung Fakultas Keguruan dan Ilmu Pendidikan, Universitas Malikussaleh. Hasil pelatihan menunjukkan peningkatan signifikan dalam keterampilan mahasiswa menggunakan CapCut dan Canva, terutama dalam menambahkan teks, overlay, efek audio, dan elemen grafis lain yang memperkuat kualitas estetika dan profesionalisme video presentasi. Selain itu, aplikasi ini mendorong mahasiswa untuk lebih kreatif dalam menyusun narasi visual yang dapat memperkuat pesan ilmiah yang disampaikan. Dengan demikian, pelatihan ini tidak hanya membekali mahasiswa dengan keterampilan teknis yang relevan, tetapi juga mendukung kesiapan mereka untuk menghadapi dunia kerja yang semakin menuntut kompetensi multimedia. Kegiatan ini diharapkan menjadi investasi jangka panjang dalam mempersiapkan lulusan yang mampu beradaptasi dengan perkembangan teknologi digital di bidang pendidikan dan komunikasi.